Călin Ioan DUȘE, Imperiul Roman și creștinismul în timpul Sfântului Ignatie Teoforul, Episcopul Antiohiei [The Roman Empire and Christianity during the Time of Saint Ignatius Theophorus, Bishop of Antioch], Cluj-Napoca, Presa Universitară Clujeană, 2022, 510 p. - TELEA , Marius (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The work The Roman Empire and Christianity during the Time of Saint Ignatius Theophorus, Bishop of Antioch, elaborated by Rev. Assoc. Prof. Dr Călin Ioan DUȘE from the Faculty of Greek Catholic Theology, Department of Oradea, Babeș–Bolyai University, Cluj-Napoca, is part of a restorative process in Romanian theology. This is in the sense of the need to delve into a significant aspect during the life of Saint Ignatius Theophorus. Hence the importance of this editorial endeavour. The present work is dedicated to Saint Ignatius of Antioch’s life, works, and teachings, also known as Theophorus, the God-bearer.